1992
DOI: 10.1111/j.1349-7006.1992.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Second Primary Cancer Following Laryngeal Cancer with Special Reference to Smoking Habits

Abstract: The risk of developing a second primary cancer following laryngeal cancer was estimated by following‐up 472 male laryngeal cancer patients for an average of 8.6 years by means of record linkage to the Osaka Cancer Registry. Of these patients, 115 developed a second cancer other than laryngeal cancer, whereas the expected number derived from the incidence rates among Osaka residents was 51.4 (relative risk (RR) = 2.2, 95% confidence interval = 1.85 2.69). Cumulative risk of developing a second primary cancer wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 5 publications
3
33
0
Order By: Relevance
“…Such site combinations can be seen in the first group in Table 5. The combination of [lip, oral cavity and pharynx] versus esophagus has been reported as significantly correlated in several papers (14,(20)(21)(22)(23) and the correlation is thought to be attributable to tobacco smoking and alcohol consumption. We also identified a marginally correlated site combination among tobacco-related cancers, [lip, oral cavity and pharynx] versus larynx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such site combinations can be seen in the first group in Table 5. The combination of [lip, oral cavity and pharynx] versus esophagus has been reported as significantly correlated in several papers (14,(20)(21)(22)(23) and the correlation is thought to be attributable to tobacco smoking and alcohol consumption. We also identified a marginally correlated site combination among tobacco-related cancers, [lip, oral cavity and pharynx] versus larynx.…”
Section: Discussionmentioning
confidence: 99%
“…In several countries, epidemiological studies on MPC based on a large-scale population-based cancer registry have provided some insights into MPC from the etiological point of view. In Japan, several studies have reported the risks of MPCs following first primary cancers (7)(8) of the colon and rectum (9), non-Hodgkin's lymphoma (10), thyroid gland (11), stomach (12)(13), pharynx and larynx (14)(15), uterine cervix (16), head and neck (17) and breast (18). Since the cancer incidence pattern in Japan is known to be very different from that in Western countries, it is hoped that these studies of MPCs in Japan will provide some additional insights into the etiology of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of esophageal carcinoma associated with multiple primary squamous cell carcinomas of the upper aerodigestive tract in series of head and neck tumor patients varies from 0% to 6.3% (1,2,3,4,5,7,8,9,10,11,12,13,14,17,18,19,22,25) ( Table 2). Furthermore, the incidence of multiple primary tumors in series of patients with squamous cell carcinoma of the esophagus ranged from 3.3% to 12.4% (2,4,9,20,21,24) ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Major risk factors in developed countries include smoking tobacco and drinking alcohol, and chewing betel quid (4,5). For tobacco smoking, a dose-response trend has been reported.…”
Section: Introductionmentioning
confidence: 99%